2017
DOI: 10.1097/md.0000000000007979
|View full text |Cite
|
Sign up to set email alerts
|

Stability study of dezocine in 0.9% sodium chloride solutions for patient-controlled analgesia administration

Abstract: Background:Dezocine, a mixed agonist/antagonist of opioid receptors, has been used in iv patient-controlled analgesia (PCA) pumps for postoperative pain control. The aim of this study was to investigate the physicochemical stability of dezocine solutions in 0.9% sodium chloride for injection for PCA administration.Methods:Solutions of dezocine (0.3, 0.45, or 0.6 mg/mL in 0.9% sodium chloride for injection) were stored in polyolefin bags and glass bottles. Their stabilities at storage conditions of 4°C for 14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…[26] It has been demonstrated that dezocine is stable for at least 1 week in 5% dextrose injection or 0.9% sodium chloride injection at room temperature. [17] No loss of dezocine was found in the previous studies during the testing. The studies also reported that most of the other tested drugs, such as ketorolac tromethamine, droperidol, fentanyl, ibuprofen and dexamethasone, were stable when combined with dezocine.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[26] It has been demonstrated that dezocine is stable for at least 1 week in 5% dextrose injection or 0.9% sodium chloride injection at room temperature. [17] No loss of dezocine was found in the previous studies during the testing. The studies also reported that most of the other tested drugs, such as ketorolac tromethamine, droperidol, fentanyl, ibuprofen and dexamethasone, were stable when combined with dezocine.…”
Section: Discussionmentioning
confidence: 90%
“…The final nominal concentrations of dezocine and tropisetron hydrochloride were 0.4 mg/mL and 0.05 mg/mL, respectively. [17,18] The selection of the concentrations of these drugs in our study was based on those used in daily practice. Three polyolefin bags and 3 glass containers containing the dezocine and tropisetron hydrochloride admixture were stored at 4°C or 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…Fang et al discovered that dezocine was stable for 3 days at room temperature (25 °C) and for up to 14 days at refrigerated temperature (4 °C) in NS for PCA administration. [18] In addition, Hu et al indicated that the mixture of dezocine injection and ketorolac tromethamine in NS was stable for at least 12 hours at room Guo and Chen • Medicine (2022) www.md-journal.com temperature. [19] Chen et al confirmed that dezocine injection mixed with tropisetron hydrochloride in NS solutions was stable for up to 2 weeks, when stored at refrigerated or room temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the side effects of these drugs, it is necessary to develop a safe and effective analgesic method. Dezocine is a partial opiate drug and is used for pain management [7]. It is a newly synthesized opioid κ receptor partial agonist with a structure similar to pentazocine.…”
Section: Effect Of Dizocine Combined With Ropivacaine Recurrent Neuromentioning
confidence: 99%